Characteristics and age‐related injury patterns of maxillofacial fractures in children and adolescents: A multicentric and prospective study. Issue 3 (11th February 2022) - Segura‐Palleres, Ignasi; Sobrero, Federica; Roccia, Fabio; de Oliveira Gorla, Luis Fernando; Pereira‐Filho, Valfrido Antonio; Gallafassi, Daniel; Faverani, Leonardo Perez; Romeo, Irene; Bojino, Alessandro; Copelli, Chiara; Duran‐Valles, Francesc; Bescos, Coro; et al.
Abstract: Background/Aims: Paediatric maxillofacial trauma accounts for 15% of all maxillofacial trauma but remains a leading cause of mortality. The aim of this prospective, multicentric epidemiological study was to analyse the characteristics of maxillofacial fractures in paediatric patients managed in 14 maxillofacial surgery departments on five continents over a 1‐year period. Methods: The following data were collected: age (preschool [0–6 years], school age [7–12 years], and adolescent [13–18 years]), cause and mechanism of the maxillofacial fracture, alcohol and/or drug abuse at the time of trauma, fracture site, Facial Injury Severity Scale score, associated injuries, day of the maxillofacial trauma, timing and type of treatment, and length of hospitalization. Statistical analyses were performed using SPSS software. Results: Between 30 September 2019 and 4 October 2020, 322 patients (male:female ratio, 2.3:1) aged 0–18 years (median age, 15 years) were hospitalized with maxillofacial trauma. The most frequent causes of the trauma were road traffic accidents (36%; median age, 15 years), followed by falls (24%; median age, 8 years) and sports (21%; median age, 14 years). Alcohol and/or drug abuse was significantly associated with males ( p  < .001) and older age ( p  < .001). Overall, 474 fractures were observed (1.47 per capita). The most affected site was the mandibular condyle in children <13 years old and the nose in adolescents. The proportion of patients who underwent open reduction and internal fixation increased with age ( p  < .001). Conclusion: The main cause of paediatric maxillofacial fractures was road traffic accidents, with the highest rates seen in African and Asian centres, and the frequency of such fractures increased with age. Falls showed an inverse association with age and were the leading cause of trauma in children 0–6 years of age. The choice of treatment varies with age, reflecting anatomical and etiological changes towards patterns more similar to those seen in adulthood.